4(5y-5)-(3y+8)=

Simple and best practice solution for 4(5y-5)-(3y+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5y-5)-(3y+8)= equation:


Simplifying
4(5y + -5) + -1(3y + 8) = 0

Reorder the terms:
4(-5 + 5y) + -1(3y + 8) = 0
(-5 * 4 + 5y * 4) + -1(3y + 8) = 0
(-20 + 20y) + -1(3y + 8) = 0

Reorder the terms:
-20 + 20y + -1(8 + 3y) = 0
-20 + 20y + (8 * -1 + 3y * -1) = 0
-20 + 20y + (-8 + -3y) = 0

Reorder the terms:
-20 + -8 + 20y + -3y = 0

Combine like terms: -20 + -8 = -28
-28 + 20y + -3y = 0

Combine like terms: 20y + -3y = 17y
-28 + 17y = 0

Solving
-28 + 17y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '28' to each side of the equation.
-28 + 28 + 17y = 0 + 28

Combine like terms: -28 + 28 = 0
0 + 17y = 0 + 28
17y = 0 + 28

Combine like terms: 0 + 28 = 28
17y = 28

Divide each side by '17'.
y = 1.647058824

Simplifying
y = 1.647058824

See similar equations:

| -9x+15=-4x-70 | | 4x^2+12x+c=y | | 5h-(h+8)=2n | | 6(5a+4)+5a=-11 | | -2(x+2)-3=5 | | -x-(13+4x)=-3(5-9x)+3k | | 2x^2+5x^2-7x-3= | | 2=4r | | 7x-(6x+5)=6x-40 | | 2x^3-6x^2-141x+6=0 | | 2(h+9)-6= | | 6-8(n-4)=-8n+37 | | 0.5x+8=3x+5 | | 10x-75=5x+30 | | w+14=18 | | 6x+10-8x=15-13x+11x-5 | | -10(-3x+3)=30+10x | | (3+x)4+(5x)=66 | | 20-0.5y=12.5 | | 20x-7-5=-52 | | -6(2+2x)=-24 | | .50x+8=3x+5 | | 0=(-4x^2-6x)-1 | | 8x+7=3x+3 | | 671.5=174.5+35.5(x-1) | | 43000=a-140000 | | x/6+94-76=31 | | 5x-40=17 | | 2x-33+5x= | | w=2d+7 | | 4x+8-7x=-1 | | 2(-c-8)=-2c-8 |

Equations solver categories